The Bonds and Burdens of Family Life:: Using Narrative Analysis to Understand Difficult Relationships - Breheny, Mary; Stephens, Christine (Narrative Matters)

(untitled) (The University of New Brunswick, 2011)
Attempts to understand difficult family relationships have ignored the inextricable links between positive and negative relationships. Narrative analysis provides insight into complex relationships within social context. We analysed interviews with older people in New Zealand using levels of narrativity to reveal the negotiations required to manage personal identity at the intersection of competing public narratives. Participants and interviewers used public narratives of family life that reinforce family roles while simultaneously drawing upon alternative narratives of identity and morality. Investigating narratives of difficult family relationships reveals the influence of dominant social norms on the negotiation of social identities through personal stories.